Relationship Between Obesity and Anti-Müllerian Hormone in Reproductive-Aged African-American Women - Bernardi, Lia A. (Obesity (Silver Spring), 2016)
OBJECTIVE: To determine whether there is an association between obesity and Anti-Müllerian hormone (AMH) amongst reproductive-aged African-American women (AAW). METHODS: 1,654 AAW aged 23–35 who participated in an ongoing NIEHS study were included. Anthropometric measurements, personal health information, and serum AMH and adipokine levels were analyzed. RESULTS: The median body mass index (BMI) was 32.4 kg/m(2) and the median AMH was 3.18 ng/mL. Participants with obesity had AMH concentrations that were 23.7% lower than those with a BMI ≤ 25 kg/m(2) (2.9 ng/mL versus 3.8 ng/mL). In multivariable linear regression models, current BMI (β=−0.015; 95% CI −0.021, −0.009), BMI at age 18 (β=−0.016; 95% CI −0.024, −0.008), heaviest reported lifetime weight (β=−0.002; 95% CI −0.003, −0.001) and leptin (β=−0.016; 95% CI −0.025, −0.007) were inversely associated with AMH. There was no significant association between adiponectin and AMH. AMH was significantly lower (mean log=0.91, SE=0.11) in participants with obesity at age 18 and at enrollment when compared to those who were underweight or normal weight at age 18 but had obesity at enrollment (mean log=1.16, SE=0.12). CONCLUSIONS: In reproductive-aged AAW there is a significant association between obesity and AMH, suggesting that excess adiposity may compromise ovarian reserve. Effects of obesity on AMH may be cumulative.